Two-component self-emulsifying polyester acrylic acid dispersion and preparation method thereof

By introducing hydrophilic monomers with cyclic carbonate groups through stepwise controlled polycondensation and graft polymerization processes, the problem of uneven particle size in two-component self-emulsifying polyester acrylic dispersions was solved, resulting in a dispersion with uniform particle size and narrow distribution, thus improving the stability and performance of the coating.

CN121378600APending Publication Date: 2026-01-23HUIZHOU SHEN SAIER CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511693967.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-18
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

In the prior art, the particle size of the two-component self-emulsifying polyester acrylic dispersion is not uniform and the particle size distribution range is wide, which affects the leveling properties, application performance and long-term storage stability of the product.

Method used

A stepwise controlled polycondensation and graft polymerization process is adopted to introduce hydrophilic monomers with cyclic carbonate groups. By controlling the reaction conditions and the order of addition, the hydrophilic monomers are uniformly anchored on the polyester backbone to form a functional resin with a zwitterionic structure. Finally, under mild conditions, it reacts with dimethylethanolamine to form a nanoscale micelle dispersion.

Benefits of technology

It achieves a narrow distribution dispersion with a particle size D50 of 50-150 nm and a PDI of <0.2, which improves storage stability and application leveling, avoids Ostwald curing, and enhances the density and water resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121378600A_ABST
    Figure CN121378600A_ABST
Patent Text Reader

Abstract

The invention discloses a two-component self-emulsifying polyester acrylic dispersion and a preparation method thereof, and relates to the field of waterborne polyurethane paints.The preparation method comprises the following steps that a half ester intermediate is prepared and reacts with ethylene carbonate, and a hydrophilic monomer with cyclic carbonate groups is obtained; dibasic acid and dihydric alcohol are subjected to polycondensation to obtain initial resin, propylene glycol monomethyl ether, a mixed solution a containing hydrophilic monomers and a mixed solution b are added into the initial resin at intervals, mixing is conducted, and functional resin is obtained; the functional resin and dimethylethanolamine are subjected to a stirring reaction, then deionized water is added, mixing is conducted, and a product with the D50 being 50-150 nm and the PDIlt is obtained; and 0.2 of a two-component self-emulsifying polyester acrylic acid dispersion. According to the preparation method disclosed by the invention, the hydrophilic monomer with a cyclic carbonate group is introduced during preparation, and a step-by-step controlled polycondensation and graft polymerization process is adopted, so that the hydrophilic monomer is directionally and uniformly anchored on a polyester main chain, and the problem of non-uniform molecular structure caused by random copolymerization of the hydrophilic monomer in a traditional method is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waterborne polyurethane coatings, and more particularly to a two-component self-emulsifying polyester acrylic dispersion and its preparation method. Background Technology

[0002] Two-component self-emulsifying polyester acrylic dispersion is the hydroxyl component of two-component waterborne polyurethane coatings. It uses water as a medium and has stable dispersibility and reactive hydroxyl groups. When used, it needs to be mixed with a polyisocyanate curing agent. Through the cross-linking reaction between hydroxyl groups and isocyanate groups, it is cured into a high-performance polyurethane coating film that combines environmental friendliness with superior physicochemical properties.

[0003] In the preparation of two-component self-emulsifying polyester-acrylic dispersions, existing technologies typically employ the random copolymerization of low-molecular-weight hydrophilic monomers (such as dimethylolpropionic acid, DMPA) into the polymer backbone to achieve self-emulsification of the resin in the aqueous phase. While this method imparts a certain degree of water dispersibility to the resin, it has some drawbacks. For example, in traditional condensation and free radical copolymerization processes, the reactivity and inoculation sites of hydrophilic monomers are random, resulting in uneven distribution throughout the polymer molecular chain. This molecular-level heterogeneity is amplified dramatically during water dispersion: molecular chain segments rich in hydrophilic groups rapidly combine with water and extend outward to form the shell of micelles; while hydrophobic segments lacking hydrophilic groups aggregate to form the core of micelles. Due to the significant differences in the hydrophilicity of each polymer chain, their nucleation rate and micelle growth process cannot be synchronized, inevitably resulting in dispersions with varying particle sizes and wide distribution ranges (polydispersity index PDI is usually greater than 0.3). The presence of large particles increases the viscosity of the system, affecting the leveling properties and application performance of the product. Furthermore, the Brownian motion rate and interfacial energy of particles of different sizes differ, making them highly susceptible to Ostwald ripening during long-term storage. This occurs when small particles gradually dissolve and redeposit on the surface of large particles, leading to the continuous growth of large particles and ultimately affecting the long-term storage stability of the dispersion and the product's shelf life.

[0004] Therefore, a two-component self-emulsifying polyester acrylic dispersion and its preparation method are proposed to solve the problems of uneven particle size and wide particle size distribution. Summary of the Invention

[0005] The purpose of this invention is to provide a two-component self-emulsifying polyester acrylic dispersion and its preparation method, which solves the problems of uneven particle size and wide particle size distribution range.

[0006] To achieve this objective, the present invention adopts the following technical solution: A method for preparing a two-component self-emulsifying polyester acrylic dispersion, the method comprising the following steps: Step S1: Prepare a half-ester intermediate and react it with ethylene carbonate to obtain a hydrophilic monomer with cyclic carbonate groups; Step S2: Polycondense a dicarboxylic acid and a diol to obtain an initial resin. Then, add propylene glycol methyl ether and a mixture containing hydrophilic monomers, and mix them with mixture b to the initial resin to obtain a functional resin. Step S3: The functional resin and dimethylethanolamine are stirred and reacted, and then deionized water is added and mixed to obtain a two-component self-emulsifying polyester acrylic dispersion with D50 of 50-150nm and PDI<0.2.

[0007] Step S1 specifically includes the following steps: Step S11: Under nitrogen atmosphere, polyethylene glycol monomethyl ether and maleic anhydride are stirred and mixed to obtain a half-ester intermediate; Step S12: Mix the semi-ester intermediate with ethylene carbonate at a first temperature to obtain a hydrophilic monomer.

[0008] In step S11, the molecular weight of the polyethylene glycol monomethyl ether is 350-550 g / mol, the temperature of the stirring and mixing a is 85-95℃ and the time is 2-4 h, and the molar ratio of the polyethylene glycol monomethyl ether to maleic anhydride is 1:(1.5-2.5). In step S12, the first temperature is 100-120℃, the molar ratio of the semi-ester intermediate to ethylene carbonate is 1:(1.0-1.2), the stirring and mixing time is 3-5h, and the pressure is 0.05-0.08MPa.

[0009] The initial resin is obtained according to the following steps: Step S211: Melt and mix the dicarboxylic acid and diol at a second temperature a under nitrogen atmosphere to obtain a mixture; Step S212: Heat the mixture to a second temperature b and maintain it, and obtain the initial resin after the actual acid value of the mixture reaches the expected acid value.

[0010] In step S211, the second temperature a is 175-185℃, the heating rate is 10-15℃ / min, and the melting and mixing rotation speed is 150-200 rpm; the dicarboxylic acid is a mixture of isophthalic acid and fumaric acid, with a molar ratio of (7-8):(2-3), and the diol is a mixture of neopentyl glycol and trimethylpentyl glycol, with a molar ratio of (6-7):(3-4); In step S212, the second temperature b is 200-210℃, the heating rate is 3-7℃ / min, the holding time is 4-8h, and the expected acid value is 8-15mgKOH / g.

[0011] The functional resin is obtained according to the following steps: Step S221: After heating the initial resin to the second temperature c, add propylene glycol methyl ether to obtain mixture a; Step S222: After mixing the mixture a with the mixture a, keep it at the second temperature c once to obtain the mixture b; Step S223: After mixing the mixture b with the mixture b, perform a second heat preservation at the second temperature c to obtain the functional resin.

[0012] In step S221, the second temperature c is 115-125℃, and the amount of propylene glycol methyl ether added is 10-15% of the initial resin solids mass. In step S222, the mixture a is a mixture of acrylate monomer a, hydrophilic monomer and benzoyl peroxide a, wherein the amount of acrylate monomer a added is 10-20% of the initial resin solids mass, the amount of hydrophilic monomer added is 5-10% of the initial resin solids mass, the amount of benzoyl peroxide a added is 1-3% of the total mass of acrylate monomer a and hydrophilic monomer, and the single heat preservation time is 1.5-2.5h; In step S223, the mixture b is a mixture of acrylate monomer b and benzoyl peroxide b, wherein the amount of acrylate monomer b added is 25-35% of the initial resin solids mass, the amount of benzoyl peroxide b added is 1-3% of the acrylate monomer b mass, and the secondary heat preservation time is 2-3 hours.

[0013] Step S3 specifically includes the following steps: Step S31: The functional resin and dimethylethanolamine are stirred and reacted at a third temperature and kept at the temperature to obtain the preform; Step S32: Maintain the third temperature, add deionized water to the preform and stir dropwise to obtain a two-component self-emulsifying polyester acrylic dispersion.

[0014] In step S31, the third temperature is 55-65℃, the heat preservation time is 1-2h, and the amount of dimethylethanolamine added is 0.95-1.05 equivalents of the molar amount of cyclic carbonate groups. In step S32, the stirring speed during the drop addition is 300-500 rpm, the temperature of the deionized water is 40-50℃, and the weight ratio of deionized water to functional resin is 1:(1.5-2.5).

[0015] A two-component self-emulsifying polyester acrylic dispersion, wherein the two-component self-emulsifying polyester acrylic dispersion is obtained by the preparation method described above.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a two-component self-emulsifying polyester-acrylic dispersion and its preparation method. By introducing hydrophilic monomers with cyclic carbonate groups during the preparation process and employing a step-by-step controlled polycondensation and graft polymerization process, the hydrophilic monomers are oriented and uniformly anchored on the polyester backbone, avoiding the molecular structure inhomogeneity problem caused by random copolymerization of hydrophilic monomers in traditional methods. Specifically, a potentially reactive hemiester intermediate is first prepared, and then cyclic carbonate end groups are introduced through a reaction with ethylene carbonate, ensuring the chemical stability of the hydrophilic monomers during subsequent copolymerization. Subsequently, the hydrophilic monomers and acrylate monomers are added to the polyester resin in stages. By controlling the reaction concentration and the temperature holding sequence, preferential grafting and deep fixation of the hydrophilic monomers are achieved, resulting in a functional resin with a uniform molecular structure. Finally, under mild conditions, a ring-opening reaction with dimethylethanolamine is used to convert the cyclic carbonate groups into a zwitterionic structure with strong interfacial activity, thereby endowing the system with self-emulsifying ability. This method achieves a particle size D50 of 50-150 without the addition of external surfactants. Narrowly distributed dispersions with nm and PDI < 0.2 improve the storage stability and leveling properties of the dispersions during application, avoid the Ostwald curing problem caused by large particles, and reduce migration and precipitation of hydrophilic monomers in the coating film due to their firm anchoring. This enhances the density, water resistance, and weather resistance of the final coating, achieving a balance between dispersion stability and film-forming performance. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] The structures, proportions, sizes, etc., shown in the accompanying drawings of this specification are only for the purpose of assisting those skilled in the art in understanding and reading the content disclosed in the specification, and are not intended to limit the conditions under which the present invention can be implemented. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in the proportions, or adjustments to the size, without affecting the effects and objectives that the present invention can produce, should still fall within the scope of the technical content disclosed in the present invention.

[0019] Figure 1 This is a flowchart of the preparation method in this invention. Detailed Implementation

[0020] To make the objectives, features, and advantages of this invention more apparent and understandable, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the embodiments described below are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0021] In the description of this invention, it should be understood that the terms "upper," "lower," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the invention. It should be noted that when a component is considered to be "connected" to another component, it can be directly connected to the other component or there may be a component positioned centrally in the connection.

[0022] Example 1: Please see Figure 1 This embodiment describes a method for preparing a two-component self-emulsifying polyester acrylic dispersion, the method comprising the following steps: Step S1: Prepare a half-ester intermediate and react it with ethylene carbonate to obtain a hydrophilic monomer with cyclic carbonate groups; Step S2: Polycondense a dicarboxylic acid and a diol to obtain an initial resin. Then, add propylene glycol methyl ether and a mixture containing hydrophilic monomers, and mix them with mixture b to the initial resin to obtain a functional resin. Step S3: The functional resin and dimethylethanolamine are stirred and reacted, and then deionized water is added and mixed to obtain a two-component self-emulsifying polyester acrylic dispersion with D50 of 50-150nm and PDI<0.2.

[0023] Specifically, in step S1, a half-ester intermediate is prepared and reacted with ethylene carbonate to obtain a hydrophilic monomer with cyclic carbonate groups. Step S1 specifically includes the following steps: Step S11: Under nitrogen atmosphere, polyethylene glycol monomethyl ether and maleic anhydride are stirred and mixed to obtain a half-ester intermediate; In step S11, the molecular weight of the polyethylene glycol monomethyl ether is 350-550 g / mol, the stirring and mixing a is carried out at a temperature of 85-95°C for 2-4 hours, and the molar ratio of the polyethylene glycol monomethyl ether to maleic anhydride is 1:(1.5-2.5); preferably, the molecular weight of the polyethylene glycol monomethyl ether is 450 g / mol, the stirring and mixing a is carried out at a temperature of 90°C for 3 hours, and the molar ratio of the polyethylene glycol monomethyl ether to maleic anhydride is 1:2. It should be noted that the hydroxyl group at the end of polyethylene glycol monomethyl ether undergoes a nucleophilic attack on the anhydride ring of maleic anhydride under thermal activation, occurring on the carbonyl carbon of the anhydride, leading to ring opening and the formation of an ester bond and a free carboxyl group. This reaction is regioselective, mainly producing monoesterified products. Conducting the reaction at a temperature of 85-95℃ ensures a sufficient reaction rate while avoiding side reactions such as the formation of diesterized products or the double bond isomerization of maleic anhydride.

[0024] It is known that the obtained half-ester intermediate possesses both nonionic polyethylene glycol hydrophilic segments and reactive carbon-carbon double bonds and carboxyl groups. This structure enables the half-ester intermediate to provide steric stability and participate in subsequent copolymerization reactions as a macromonomer. The mild reaction conditions ensure high conversion rate and product consistency, simplifying post-processing steps. The half-ester intermediate can be used directly in the next reaction without purification, improving process efficiency.

[0025] Understandably, the pre-construction of hydrophilic units through chemical bonding lays the foundation for uniform and firm anchoring on the initial resin, avoiding problems such as migration and precipitation caused by physical mixing of emulsifiers. This is the primary prerequisite for achieving particle size uniformity. In addition, the selection of polyethylene glycol monomethyl ether with a molecular weight of 350-550 g / mol is to achieve a balance between the length of the hydrophilic chain segment and the water resistance of the coating film (formed after curing based on the coating obtained from the dispersion). If the chain segment is too short, the emulsification efficiency will be insufficient, while if it is too long, although it is beneficial to the dispersion stability, it will seriously impair the water resistance due to the excessive hydrophilic ether bonds remaining in the coating film.

[0026] Step S12: Mix the semi-ester intermediate with ethylene carbonate at a first temperature to obtain a hydrophilic monomer.

[0027] In step S12, the first temperature is 100-120℃, the molar ratio of the half-ester intermediate to ethylene carbonate is 1:(1.0-1.2), the stirring and mixing time b is 3-5h, and the pressure is 0.05-0.08MPa; preferably, the first temperature is 110℃, the molar ratio of the half-ester intermediate to ethylene carbonate is 1:1.1, the stirring and mixing time b is 4h, and the pressure is 0.07MPa.

[0028] It should be noted that the highly reactive anhydride group remaining in the half-ester intermediate molecule acts as a strong electrophile, attacking the carbonyl carbon atom in the ethylene carbonate molecule, initiating the ring-opening of the ethylene carbonate ring structure, and covalently bonding the cyclic carbonate group to the end of the molecular chain through esterification. In addition, the above reactions are carried out at a temperature of 100-120℃ and a pressure of 0.05-0.08MPa to prevent excessive volatilization of low-boiling-point ethylene carbonate, ensure the accuracy of the reactant ratio, and thus improve the yield.

[0029] It is known that the cyclic carbonate groups at the ends of the hydrophilic monomer are chemically stable at room temperature and polymerization temperature, and will not interfere with the free radical polymerization reaction. This ensures that the hydrophilic monomer will not undergo side reactions in the subsequent step S2, thereby ensuring the controllability and repeatability of the polymerization process, which is a prerequisite for obtaining batch-stable dispersions.

[0030] Specifically, in step S2, a dicarboxylic acid and a diol are polycondensed to obtain an initial resin, and then propylene glycol methyl ether, a mixture containing hydrophilic monomers, and a mixture b are added to the initial resin in a condensation process to obtain a functional resin. The initial resin is obtained according to the following steps: Step S211: Melt and mix the dicarboxylic acid and diol at a second temperature a under nitrogen atmosphere to obtain a mixture; In step S211, the second temperature a is 175-185℃, the heating rate is 10-15℃ / min, and the melting and mixing rotation speed is 150-200 rpm; the dicarboxylic acid is a mixture of isophthalic acid and fumaric acid, with a molar ratio of (7-8):(2-3), and the diol is a mixture of neopentyl glycol and trimethylpentyl glycol, with a molar ratio of (6-7):(3-4); preferably, the second temperature a is 180℃, the heating rate is 13℃ / min, and the melting and mixing rotation speed is 180 rpm; the molar ratio of isophthalic acid to fumaric acid is 7.5:2.5, and the molar ratio of neopentyl glycol to trimethylpentyl glycol is 6.5:3.5; Step S212: Heat the mixture to a second temperature b and maintain it, and obtain the initial resin after the actual acid value of the mixture reaches the expected acid value.

[0031] In step S212, the second temperature b is 200-210℃, the heating rate is 3-7℃ / min, the holding time is 4-8h, the expected acid value is 8-15mgKOH / g, and the initial resin is a hydrophobic unsaturated polyester oligomer with a number average molecular weight of 800-1500g / mol and containing residual carbon-carbon double bonds of fumaric acid on the chain; preferably, the second temperature b is 200℃, the heating rate is 5℃ / min, and the holding time is 6h.

[0032] It should be noted that isophthalic acid, fumaric acid, neopentyl glycol, and trimethylpentyl glycol undergo multiple esterification condensation reactions, forming ester bonds by removing water molecules and gradually connecting to form long-chain polymers. Among them, the carbon-carbon double bonds provided by fumaric acid are retained on the polymer backbone.

[0033] It is worth noting that isophthalic acid provides a rigid structure and heat resistance, while fumaric acid provides unsaturated double bonds for subsequent grafting. The molar ratio of the two is controlled at (7-8):(2-3) to ensure that there are enough unsaturated points to participate in grafting, while avoiding excessive rigidity of the main chain. Neopentyl glycol and trimethylpentyl glycol both provide branched structures and excellent hydrolysis resistance. Their molar ratio (6-7):(3-4) helps to adjust the flexibility and viscosity of the oligomer.

[0034] It is known that the initial resin is a polyester oligomer with a moderate molecular weight, containing unsaturated double bonds in the chain, and exhibiting overall hydrophobicity. This oligomer has a suitable viscosity and high compatibility with the subsequently added acrylate monomers. In addition, the heating methods in steps S211 and S212 prevent the dibasic acid from sublimating due to excessively rapid heating, ensuring the stability and uniformity of the reaction. Furthermore, the actual acid value of the mixture allows for effective control of the degree of polymerization. Correspondingly, the actual acid value is obtained using an acid value meter.

[0035] Understandably, the absence of any permanent hydrophilic monomers in the initial resin creates favorable conditions for subsequent steps, preventing the resin's own structure from becoming inhomogeneous due to the random distribution of hydrophilic groups. This is the structural basis for solving the problem of wide particle size distribution in the final dispersion.

[0036] The functional resin is obtained according to the following steps: Step S221: After heating the initial resin to the second temperature c, add propylene glycol methyl ether to obtain mixture a; In step S221, the second temperature c is 115-125°C, and the amount of propylene glycol methyl ether added is 10-15% of the initial resin solids mass; preferably, the second temperature c is 120°C, and the amount of propylene glycol methyl ether added is 13% of the initial resin solids mass. Step S222: After mixing the mixture a with the mixture a, keep it at the second temperature c once to obtain the mixture b; In step S222, the mixture a is a mixture of acrylate monomer a (without hydroxyl groups), hydrophilic monomer, and benzoyl peroxide a. The amount of acrylate monomer a added is 10-20% of the initial resin solids mass, the amount of hydrophilic monomer added is 5-10% of the initial resin solids mass, and the amount of benzoyl peroxide a added is 1-3% of the total mass of acrylate monomer a and hydrophilic monomer. The initial heat treatment time is 1.5-2.5 hours. Preferably, acrylate monomer a is a mixture of methyl methacrylate and butyl acrylate, the amount of acrylate monomer a added is 15% of the initial resin solids mass, the amount of hydrophilic monomer added is 8% of the initial resin solids mass, and the amount of benzoyl peroxide a added is 2% of the total mass of acrylate monomer a and hydrophilic monomer. The initial heat treatment time is 2 hours. Step S223: After mixing the mixture b with the mixture b, perform a second heat preservation at the second temperature c to obtain the functional resin.

[0037] In step S223, the mixture b is a mixture of acrylate monomer b (containing hydroxyl groups) and benzoyl peroxide b, wherein the amount of acrylate monomer b added is 25-35% of the initial resin solids mass, the amount of benzoyl peroxide b added is 1-3% of the acrylate monomer b mass, the secondary heat preservation time is 2-3 hours, and the functional resin is a polyester-acrylic hybrid resin solution containing cyclic carbonate groups and hydroxyl groups; preferably, the acrylate monomer is hydroxyethyl acrylate or hydroxypropyl acrylate, the amount of acrylate monomer b added is 30% of the initial resin solids mass, the amount of benzoyl peroxide b added is 2% of the acrylate monomer b mass, and the secondary heat preservation time is 2.5 hours.

[0038] It should be noted that the initial resin is mixed with propylene glycol methyl ether to reduce viscosity, then mixture a is added and kept at a temperature for 1.5-2.5 hours to ensure preferential grafting of hydrophilic monomers. Finally, mixture b is added and kept at a temperature for 2-3 hours to ensure complete polymerization. Specifically, under the action of benzoyl peroxide, the acrylate monomers in mixture a copolymerize with the hydrophilic monomers and preferentially graft onto the unsaturated double bond positions on the polyester chain of the initial resin, thus anchoring the hydrophilic monomers. Subsequently, after the addition of mixture b, the acrylate monomers continue to polymerize, growing the polymer chain and completing the construction of the entire functional resin.

[0039] It is known that the hydrophilic monomers are uniformly and firmly anchored to the polymer backbone of the initial resin through chemical bonds, rather than through physical doping. At the same time, the order of addition of mixture a and mixture b actively controls the reaction competition rate of different monomers, ensuring that the hydrophilic monomers can be effectively embedded into the polymer network, thus realizing the fine construction and controllable synthesis of functional resin molecular structures.

[0040] Understandably, step S2 ensures that each functional resin molecule chain contains hydrophilic monomers in similar proportions and with strong anchorage. This enables all resin particles to form micellar structures in the aqueous phase with highly consistent hydrophilic shell thickness and properties during the subsequent self-emulsifying dispersion process, resulting in a dispersion with a D50 of 50-150 nm and a PDI of <0.2. This eliminates the uneven nucleation and growth caused by the randomness of the distribution of hydrophilic groups.

[0041] It is important to emphasize that the method of adding materials in step S2 ensures that the hydrophilic monomers copolymerize at a lower polymerization concentration, thereby increasing their chances of reacting with unsaturated sites on the polyester chain. This achieves preferential grafting and deep anchoring, which is the core process guarantee for obtaining monodisperse particles (PDI<0.2). This method achieves the targeted grafting of functional monomers by actively controlling the reaction reactivity ratio. In step S222, the concentration of acrylate monomers in the reaction system is low, and the hydrophilic macromonomers have a higher probability of reacting with the limited number of unsaturated double bonds on the polyester chain, thereby achieving preferential and firm chemical anchoring. If steps S222 and S223 are combined and all monomers are added at once, due to the difference in reactivity ratio, the hydrophilic monomers cannot be effectively grafted onto the polyester backbone. Instead, they tend to homopolymerize on their own or copolymerize with acrylates, causing the distribution of hydrophilic units on the molecular chain to return to a random state, which cannot solve the fundamental problem of wide particle size distribution.

[0042] In summary, in step S2, by not introducing permanent hydrophilic monomers and controlling the acid value of the polycondensation reaction, a uniform hydrophobic resin skeleton is obtained, eliminating the initial structural inhomogeneity caused by the random distribution of hydrophilic groups during the polycondensation stage. This lays the foundation for the formation of a uniform micelle core. In the subsequent steps, mixture a is added first, followed by mixture b, ensuring that the hydrophilic monomers can preferentially and fully react with the unsaturated points on the initial resin, allowing them to be deeply and uniformly anchored in the polymer network. This overcomes the problem of uneven copolymerization caused by different polymerization rates when all monomers are added at once, thus ensuring that each resin molecular chain contains hydrophilic units with similar proportions and positions.

[0043] Specifically, in step S3, the functional resin is stirred and reacted with dimethylethanolamine, and then deionized water is added and mixed to obtain a two-component self-emulsifying polyester acrylic dispersion with a D50 of 50-150nm and a PDI of <0.2.

[0044] Step S3 specifically includes the following steps: Step S31: The functional resin and dimethylethanolamine are stirred and reacted at a third temperature and kept at the temperature to obtain the preform; In step S31, the third temperature is 55-65℃, the holding time is 1-2h, the amount of dimethylethanolamine added is 0.95-1.05 equivalents of the molar amount of cyclic carbonate groups, and the preform is a resin solution containing zwitterionic hydrophilic centers (carboxylate and quaternary ammonium ions); preferably, the third temperature is 60℃, the holding time is 1.5h, and the amount of dimethylethanolamine added is 1.03 equivalents of the molar amount of cyclic carbonate groups; It should be noted that the tertiary amino group in the dimethylethanolamine molecule acts as a nucleophile, attacking the carbonyl carbon on the cyclic carbonate group at the end of the hydrophilic monomer in the functional resin, causing the three-membered ring strain to open, generating a β-hydroxycarbamate structure containing hydroxyl and quaternary ammonium cations. This reaction converts the stable cyclic carbonate into a strongly hydrophilic zwitterionic structure (carboxylate and quaternary ammonium ions coexist). At a mild temperature of 55-65℃, dimethylethanolamine is slowly added to the functional resin and stirred for 1-2 hours to ensure that the cyclic carbonate group is fully and quantitatively converted.

[0045] It is known that the functional resin is activated from a potentially hydrophilic state to a strongly hydrophilic state, and a zwitterionic hydrophilic centers with high emulsification efficiency are formed on the molecular chain. Through the synergistic effect of electrostatic repulsion (ion pairs) and steric hindrance (polyether chain), the zwitterionic structure has a higher emulsification efficiency than traditional single ionic emulsifiers. This is directly reflected in the fact that, with the same amount of hydrophilic monomer, the dispersion obtained in this embodiment has a smaller particle size and a narrower distribution; or, to achieve the same particle size and stability, the amount of hydrophilic monomer required in this embodiment is less, thereby bringing better water resistance to the final coating film.

[0046] It should also be noted that the formed zwitterionic hydrophilic centers have extremely high interfacial activity. They can not only stabilize the dispersion itself, but also effectively emulsify it when the dispersion is mixed with a pure hydrophobic aliphatic polyisocyanate curing agent that has not undergone hydrophilic modification, forming a uniform co-dispersion system. This solves the problem of poor compatibility between traditional waterborne hydroxyl resins and hydrophobic curing agents, which easily leads to coating surface defects. At the same time, it avoids the cost of complex hydrophilic modification of the curing agent.

[0047] Understandably, the hydrophilic centers of zwitterions provide electrostatic and steric stability superior to traditional emulsifiers. This ensures the formation of stable and uniform micelles during subsequent water dispersion. At the same time, the newly generated hydroxyl groups increase the crosslinking density, ensuring that the final dispersion has excellent storage stability and monodispersity.

[0048] Step S32: Maintain the third temperature, add deionized water to the preform and stir dropwise to obtain a two-component self-emulsifying polyester acrylic dispersion.

[0049] In step S32, the stirring speed during the drop addition is 300-500 rpm, the temperature of the deionized water is 40-50℃, and the weight ratio of deionized water to functional resin is 1:(1.5-2.5); preferably, the stirring speed during the drop addition is 400 rpm, the temperature of the deionized water is 45℃, and the weight ratio of deionized water to functional resin is 1:2.

[0050] It should be noted that under moderate shear force of 300-500 rpm, water molecules gradually penetrate into the preform. When the water volume reaches a critical value, a phase transition occurs. The hydrophobic segments of the preform aggregate to form the core of micelles, while the hydrophilic zwitterionic segments align towards the aqueous phase to form a stable shell, thus spontaneously forming a nanoscale water-in-oil colloidal dispersion system. In addition, by controlling the temperature and addition rate of deionized water, particle aggregation or widening of particle size distribution caused by excessive local water volume or uneven shear can be effectively prevented, ensuring the uniformity and stability of the dispersion process.

[0051] It is known that the temperature of deionized water is controlled at 40-50℃ in order to form a suitable temperature difference with the preform. Too low a temperature may cause the resin viscosity to increase instantaneously, which is not conducive to the uniform diffusion of the aqueous phase and the phase transformation. Too high a temperature may promote the vaporization of water or low-boiling-point components produced by the aminolysis reaction and introduce bubbles. In addition, the addition rate of deionized water should be controlled at 10-15% / min of the total water volume, and it should be added at a slower rate in the early stage. After the critical point of the system changing from water in oil to oil in water, the addition rate can be appropriately accelerated.

[0052] In summary, in step S3, after the functional resin is formed, the cyclic carbonate groups are converted into a strongly hydrophilic zwitterionic structure. This avoids the instability caused by prematurely introducing hydrophilic ionic groups during high-temperature polymerization (the second temperature c in step S221). If this reaction is carried out before or during polymerization, the generated ionic groups will cause a sharp increase in the viscosity of the system and may interfere with the normal chain growth of free radical polymerization, leading to side reactions and non-uniform molecular chain structure. This non-uniform polymer structure formed in the early stage is the direct cause of the wide particle size distribution in the subsequent dispersion stage. Through the above method, the polymer is synthesized in a pure and stable hydrophobic environment, thereby obtaining a precursor with a uniform structure. After step S, all resin molecular chains have a zwitterionic hydrophilic shell with highly consistent properties and density. Under controlled shear force and water temperature, they can undergo phase transformation synchronously to form a uniform and stable micelle dispersion.

[0053] The following is a comparison of various data between the two-component self-emulsifying polyester acrylic dispersion (Group A) of this invention and the dispersion prepared by the conventional method (Group B). Table 1 compares the particle size and distribution properties of Group A and Group B. Solid content was tested according to GB / T 1725-2007 using a halogen moisture analyzer; pH value was tested according to GB / T1717-1986 using a precision pH meter; average particle size and particle size distribution were tested according to ISO 22412 using a laser particle size analyzer; and Brookfield viscosity was tested according to GB / T 2794-2013 using a rotational viscometer.

[0054] As shown in Table 1, Group A has smaller particle size and narrower distribution than Group B, indicating that the above preparation steps have achieved uniform and firm anchoring of hydrophilic groups on the polymer molecular chain, eliminating the problem of uneven initial structure caused by random distribution of hydrophilic groups in traditional methods.

[0055] Table 2 shows the stability comparison between Group A and Group B. Thermal storage stability was tested using a constant temperature oven; particle size change rate was tested using a laser particle size analyzer according to ISO 22412; viscosity change rate was tested using a rotational viscometer according to GB / T 2794-2013.

[0056] As shown in Table 2, Group A has lower particle size change rate and viscosity change rate compared to Group B. Group A has good structural stability and anti-aging ability. The uniform nanoparticle structure of Group A effectively inhibits Ostwald ripening phenomenon and can solve the problem of short shelf life caused by particle growth, precipitation, and drastic viscosity changes during storage in Group B.

[0057] Table 3 compares the coatings made from Group A and Group B. The hardness of the pendulum rod was tested according to GB / T 1730-2007 using a pendulum rod damping tester; the gloss was tested according to GB / T9754-2007 using a gloss meter; the water resistance was tested according to GB / T 5209-1985 using a constant temperature and humidity chamber; and the ethanol wiping resistance was tested according to GB / T 23989-2009 using a wiping tester.

[0058] As shown in Table 3, Group A has higher parameters than Group B, indicating that the hydrophilic monomers in Group A participate in the reaction after curing, enhancing the crosslinking network. The good water resistance indicates that the hydrophilic groups have been transformed into hydrophobic structures after the corresponding coating has been cured and formed a film. Furthermore, the good compatibility between Group A and the hydrophobic curing agent also provides flexibility.

[0059] Example 2: This embodiment describes a two-component self-emulsifying polyester acrylic dispersion, which is obtained using the preparation method described in Example 1.

[0060] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A process for the preparation of a two-component self-emulsifying polyester acrylic dispersion, characterized in that, The preparation method comprises the following steps: Step S1, preparing a half-ester intermediate and reacting it with ethylene carbonate to obtain a hydrophilic monomer with a cyclic carbonate group; Step S2, polycondensing a dibasic acid with a dibasic alcohol to obtain an initial resin, and then adding propylene glycol methyl ether, a mixed solution a comprising the hydrophilic monomer, and a mixed solution b into the initial resin to obtain a functional resin; Step S3, stirring and reacting the functional resin with dimethyl ethanolamine, and then mixing with deionized water to obtain a two-component self-emulsifying polyester acrylic dispersion with a D50 of 50-150 nm and a PDI of less than 0.

2.

2. The method for preparing the two-component self-emulsifying polyester acrylic dispersion according to claim 1, characterized in that, The step S1 specifically comprises the following steps: Step S11, stirring and mixing polyethylene glycol monomethyl ether with maleic anhydride in a nitrogen environment to obtain a half-ester intermediate; Step S12, stirring and mixing the half-ester intermediate with ethylene carbonate at a first temperature to obtain a hydrophilic monomer.

3. The method for preparing the two-component self-emulsifying polyester acrylic dispersion according to claim 2, characterized in that, In the step S11, the molecular weight of the polyethylene glycol monomethyl ether is 350-550 g / mol, the stirring and mixing a is performed at a temperature of 85-95 ℃ for 2-4 h, and the molar ratio of the polyethylene glycol monomethyl ether to the maleic anhydride is 1:(1.5-2.5); In the step S12, the first temperature is 100-120 ℃, the molar ratio of the half-ester intermediate to the ethylene carbonate is 1:(1.0-1.2), the stirring and mixing b is performed for 3-5 h at a pressure of 0.05-0.08 MPa.

4. The method for preparing the two-component self-emulsifying polyester acrylic dispersion according to claim 1, characterized in that, The initial resin is obtained according to the following steps: Step S211, melt mixing a dibasic acid with a dibasic alcohol at a second temperature a in a nitrogen environment to obtain a mixture; Step S212, heating the mixture to a second temperature b and maintaining, and obtaining an initial resin after the actual acid value of the mixture reaches a predicted acid value.

5. The method for preparing the two-component self-emulsifying polyester acrylic dispersion according to claim 4, characterized in that, In the step S211, the second temperature a is 175-185 ℃, the heating rate thereof is 10-15 ℃ / min, and the rotation speed of the melt mixing is 150-200 rpm; the dibasic acid is a mixture of isophthalic acid and fumaric acid with a molar ratio of (7-8):(2-3), and the dibasic alcohol is a mixture of neopentyl glycol and trimethyl pentanediol with a molar ratio of (6-7):(3-4); In the step S212, the second temperature b is 200-210 ℃, the heating rate thereof is 3-7 ℃ / min, the maintaining time is 4-8 h, and the predicted acid value is 8-15 mgKOH / g.

6. The method for preparing the two-component self-emulsifying polyester acrylic dispersion according to claim 1, characterized in that, The functional resin is obtained according to the following steps: Step S221, heating the initial resin to a second temperature c and then adding propylene glycol methyl ether to obtain a mixture a; Step S222, mixing the mixed solution a with the mixture a, and then performing one-time heat preservation at the second temperature c to obtain a mixture b; Step S223, mixing the mixed solution b with the mixture b, and then performing two-time heat preservation at the second temperature c to obtain a functional resin.

7. The method for preparing the two-component self-emulsifying polyester acrylic dispersion according to claim 6, characterized in that, In the step S221, the second temperature c is 115-125 ℃, and the addition amount of the propylene glycol methyl ether is 10-15% of the mass of the solid content of the initial resin. In the step S222, the mixed solution a is a mixed solution of the acrylate monomer a, the hydrophilic monomer and the benzoyl peroxide a, wherein the acrylate monomer a is added in an amount of 10-20% of the mass of the initial resin solid content, the hydrophilic monomer is added in an amount of 5-10% of the mass of the initial resin solid content, and the benzoyl peroxide a is added in an amount of 1-3% of the total mass of the acrylate monomer a and the hydrophilic monomer, and the first holding time is 1.5-2.5 h. In the step S223, the mixed solution b is a mixed solution of the acrylate monomer b and the benzoyl peroxide b, wherein the acrylate monomer b is added in an amount of 25-35% of the mass of the initial resin solid content, and the benzoyl peroxide b is added in an amount of 1-3% of the mass of the acrylate monomer b, and the second holding time is 2-3 h.

8. The method for preparing the two-component self-emulsifying polyester acrylic dispersion according to claim 1, characterized in that, The step S3 specifically comprises the following steps: In the step S31, the third temperature is 55-65℃, the holding time is 1-2 h, and the dimethyl ethanolamine is added in an amount of 0.95-1.05 equivalent of the molar amount of the cyclic carbonate group. In the step S32, the stirring speed of the dropwise stirring is 300-500 rpm, the temperature of the deionized water is 40-50℃, and the weight ratio of the deionized water to the functional resin is 1: (1.5-2.5).

9. The method for preparing the two-component self-emulsifying polyester acrylic dispersion according to claim 1, characterized in that, The two-component self-emulsifying polyester acrylic dispersion is obtained by the preparation method according to any one of claims 1-9. ​ 10. A two-component self-emulsifying polyester acrylic dispersion characterized in that, ​